Estimation of serum 25 hydroxy vitamin D level and its correlation with metabolic and endocrine dysregulation in women with PCOS - Solanki, Vandana; Chaurasia, Amrita; Singh, Shalini; Sachan, Shikha; Varma, Kachnar; Devi, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovarian syndrome is the most common hormonal disturbance in the reproductive age women, with prevalence of 5-10%. Vitamin D deficiency is common in women with or without PCOS. The aim of this study was to assess association of serum vitamin D level with metabolic and endocrine dysregulation in women with PCOS. Methods: This cross-sectional study was done over a period of one year. 100 women of age group 20-40 years were divided in group A 30 (BMI >30 mg/m2) with PCOS, group B 20 (BMI <25 mg/m2) with PCOS, group C 50 controls and were investigated for serum FSH, LH, LH/FSH ratio, S. total testosterone, S. postprandial insulin level, glucose insulin ratio, 25 hydroxy vitamin D level. Results: LH/FSH ratio >2 (33.33% in obese and 50% in non-obese), serum total testosterone level >0.8ng/ml (80% in obese and 75% in non-obese) (p value was significant between study group as well as between study and control group). Serum fasting, postprandial blood glucose, postprandial serum insulin level was elevated in obese than non-obese PCOS. 25 (OH) vitamin D deficiency <20 ng/ml (56.675% in obese and 45% in non-obese). So, vitamin D deficiency was more common in obese PCOS. Conclusions: PCOS is more common in age group of 20-40 years. There is more Insulin resistance in obese PCOS as compared to non-obese PCOS. Vitamin D deficiency is comparatively more common in obese PCOS population than in non-obese PCOS.